Pendekatan CRT untuk Meningkatkan Motivasi dan Hasil Belajar Matematika Siswa Kelas VIII C SMPN 6 Salatiga - Khoiriyah, Umi; Mulyani, Sri; Pratama, Fika Widya (Jurnal Riset Pembelajaran Matematika, 2025)
Low Learning Outcomes and Student Learning Motivation in the Pre-Cycle of Exponent Properties Material: The Importance of Teachers' Role in Addressing the IssueThe low learning outcomes and student learning motivation in the pre-cycle of exponent properties material are crucial roles for teachers to address. One of the causes of this problem is the conventional teaching method. This study is a solution to this issue, using the Culturally Responsive Teaching (CRT) approach with a Problem-Based Learning (PBL) model. The research aims to enhance student motivation and learning outcomes in mathematics for the exponent properties material through CRT in a PBL model. The research method is Collaborative Classroom Action Research (PTKK) conducted over two cycles. Each cycle consists of two meetings and four stages: planning, implementation, observation, and reflection. The subjects of this study are 30 students from class VIII C of SMP Negeri 6 Salatiga during the first semester of the 2024/2025 academic year. The data collection techniques used in this study include questionnaires and tests. The results show that more than 50% of the students have achieved high learning motivation. The learning outcomes also improved, with a 40% classical learning achievement in the first cycle increasing to 80% in the second cycle. Thus, learning with the CRT approach in a PBL model can enhance student motivation and learning outcomes in mathematics for class VIII C of SMP Negeri 6 Salatiga.